The Failure of Syria Government Responsibilities toward Internally Displaced People (IDPs) during 2017-2019 - Khofifah, Winda; Rohma, Masitoh Nur (Global Strategis, 2025)
This article explores the issues of civil war and the forced relocation of individuals that have led to human rights abuses against Internally Displaced People (IDPs) in Syria. These occurrences began when the Syrian government initiated an offensive against the anti-government protest movement led by Bashar al-Assad. Under the guise of suppressing the uprising, the Syrian government has targeted civilians and committed various human rights violations. This article seeks to provide an in-depth analysis of the Syrian government’s responsibilities in safeguarding the status and rights of IDPs and in preventing internal displacement within Syria. Utilizing Jamie Draper’s concept of “justice and internal displacement,” this article employs a qualitative research methodology with a case study framework. The results of this article indicate the government’s inability to avert the influx of displaced individuals and its failure to meet its obligations regarding the rights of IDPs in Syria, along with the lack of sufficient protection following their displacement. Keywords: IDPs, Syria Government, Human Rights, Internal Displacement Artikel ini mengkaji isu perang saudara dan pengungsian paksa yang telah mengakibatkan pelanggaran hak asasi manusia terhadap para pengungsi internal (Internally Displaced People/IDPs) di Suriah. Peristiwa tersebut dipicu pasca-Pemerintah Suriah melancarkan serangan terhadap gerakan protes anti-pemerintahan Bashar al-Assad. Pemerintah Suriah telah menargetkan warga sipil dan berujung pada pelanggaran hak asasi manusia dengan dalih membatasi gerakan pemberontakan. Artikel ini bertujuan untuk memberikan analisis komprehensif mengenai peran Pemerintah Suriah dalam melindungi status dan hak IDPs; serta pencegahan pemindahan internal di Suriah. Dengan menggunakan konsep “justice and internal displacement” yang dikemukakan oleh Jamie Draper, artikel ini menggunakan metodologi kualitatif dengan pendekatan studi kasus. Temuan artikel ini mengungkap adanya kegagalan pemerintah dalam mencegah kedatangan dan pemenuhan tanggung jawab atas hak-hak IDPs di Suriah, serta ketiadaan perlindungan yang memadai setelah terjadinya pemindahan. Kata-kata Kunci: IDPs, Pemerintah Suriah, Hak Asasi Manusia, Pemindahan Internal